Simulation and Dynamic Response Analysis of Gear Nonlinear System - Xiao Weizhong; Chen Haixu; Yan Shidang; Zhi Yanfeng; Yu Feipeng (Jixie chuandong)
Considering the factors such as complex alternating load,meshing stiffness,meshing clearance,manufacturing and installation errors,the nonlinear multi-degree-of-freedom dynamics model of the clearance between the gear pair of the bridge crane reducer under complex excitation is established. By using the Runge-Kutta method of MATLAB/Simulink,the simulation solution of the nonlinear dynamic model of gear clearance is carried out. The effects of parameters such as load,tooth backlash,excitation frequency and damping ratio on the dynamic performance of the system are analyzed.